Mythology of gods: origin and development of the concept of gods in Indian religion - Hewamanage, Wimal; Sang, Jingyu (My University, 2015)
The existence of god or gods is one of the crucial subjects in the field of religious studies. This paper is centered on the origin of the concept of gods in the Indian religions and how it has developed during its history through a variety of myths. Though Jainism and Buddhism are clearly different from Hinduism, they are also Indian religions. This research will be limited only to Hinduism. Indian religions believe in many gods and goddesses but adherents can notably believe in one particular god and the rest are allowed by him or her unlike in the monotheistic religions. Since there are many gods in Hinduism the paper will focus on only six prominent gods namely; Agni, Indra, Varuna, Brahma, Viṣṇu and Ṡiva. The origin of the gods in Hinduism is basically threefold; wonder of nature, hero worship and religious concept. Agni, Indra and Varuṇa are appropriate examples respectively. From the very beginning of the Indian religions, there were prominent gods and it seems clear that these three gods are made by man. In the course of time, there appear three other prominent gods; Brahma, the creator of the world, Viṣṇu, the sustainer of the world and Ṡiva, the destroyer of the world. All these gods‟ weapons, chariots and body features etc. represent the imagination of Indian environmental and social characteristics. Consequently, they created gods with many faces and many hands to emphasize their power. They attributed vehicles, weapons, consorts and abodes to the gods with a variety of myths and it was similar to a man who has a healthy and wealthy life in this world. Understanding of these mythologies will be helpful to open reader‟s mind and to see the beauty and meaning of religious mythologies.
Keywords: Mythology of Gods: Origin and Development of the Concept of Gods in Indian Religion